Wormlion Vermileo vermileo (l.) (Diptera: Vermileonidae) in Slovenia and Croatia - Devetak, Dušan (Annales. Series historia naturalis, 2008)
The occurrence of the wormlion species Vermileo vermileo (Linneeus, 1758) is confirmed for the Mediterranean region of Slovenia and Croatia. Its predatory larvae were found in substrates consisting of fine sand or powder, where they construct pitfall traps similar to those of antlions. Wormlion larvae were reared in laboratory to study their biology.
Keywords: Croatia; črvasti volkec; dvokrilci; Hrvaška; Slovenia; Slovenija; Vermileo; volkci; zoologija; zoology